SARI BUAH SALAK: USAHA PENINGKATAN PENDAPATAN MASYARAKAT KAMPUNG DINDEY, DISTRIK WARMARE, KABUPATEN MANOKWARI - Suwito Suwito; Suharno Suharno; Puguh Sujarta (JURNAL PENGABDIAN PAPUA, 2018)
Increased community income from the diversification of snake fruit (salak) needs to be done. Snake fruit (Salacca edulis) is one type of fruit in Indonesia whose distribution is quite wide. The potential utilization as a beverage is very good. The purpose of this activity is to make snake fruit juice (Sabulak) as an effort to increase the income of community in the Dindey village, Warmare District, Manokwari Regency. The results of this activity were able to increase public knowledge about how to make sabulak. Knowledge of the use of fresh snake fruit used as beverage products increased from 18.2% to 100.0%. Most of the community (93.8%) said they had never known snake fruit juice drink products. Snake fruit juice is a term used for snake fruit products that are used as beverage ingredients. In fact, 100% of the people in Dindey village, Warmare District have never consumed and produced snake fruit juice. This activity increases community knowledge and motivation to increase their income through diversification of salak fruit. Key words: Salacca edulis, juice, Dindey, Warmare, community income.